Export Opportunities and Competitiveness of Textile Products - Marlenovna, Makhmudova Dilfuza (Universitas Muhammadiyah Sidoarjo, 2019)
This paper makes analyses the export opportunities and competitiveness of textile products. In this case, research has been making quotations on different points. Methodological and theoretical background was stated in the research analyses of the author. Conclusion fo the competitiveness index in the textile industry was stated to make further development as the whole.